Mining industry impacts on surface water quality in south part of Armenia. (13th September 2019) - Nalbandyan, Marine
This paper deals with the quality of water of one of the tributaries of the river Araks-River Voghchi and its watershed basin. This article covers an investigation of common ions (Ca, Mg, Na, Cl, K, SO4, HCO3 ) and HMs (Cu, Mo, Cr, Ni, Mn, Zn, Co, Cd, Pb, Ag, Hg, As) in waters of the River Voghchi and its tributaries. The performed river water research was underpinned by monthly monitoring data for 2003-2011. The impact of pollution sources and water quality formation factors were indicated. Assessment of the river water pollution with common ions and HMs were carried out, and dominating elements were indicated. The paper is highlight pollution level of the river water for the period of unstable economy and period of their stabilisation, giving the comparative analysis of river water pollution.